The Social and Political Conditions of the Region of Laghouat during the Ottoman Rule of Algeria through the Journey of Hajj Ibn Eddine Laghouati - Moussaab DJAAFOURA; Noureddine BENDOUMA (Social Sciences Journal, 2023)
This article aims to highlight the journey of Hajj Ibn Eddine Laghouati marked as "Laghouati’s journey in Northern Africa, Sudan and Diriyah" which is one of the most important historical sources that tackled the region of Laghouat during the Ottoman era.What we will focus on in the journey of Ibn Eddine is his talk about the city of Laghouat in the Ottoman era and its neighboring areas like Tadjmout, Ein Madhi and Djbel Ammour by offering and extracting the most important data related to: the location and the area- urbanism and public facilities - political and military life – economic life - social and cultural conditions such as population, tribes and language... etc. And because the main task of the historian after checking out the historical narrations, and scrutinizing the report and whether the statement is valid or false, after going through a clear and well-defined scientific approach, we will objectively evaluate what was stated in the journey of Ibn Eddine Laghouati without detracting from the value of the author.